SAT0328 Treatment of Vaginal Dryness in Women Affected by Systemic Sclerosis and Effects on Sexual Discomfort. (10th June 2014) - Muratore, M.; Carati, D.; Quarta, L.; Quarta, E.; Grimaldi, A.; Costanza, D.; Tinelli, A.
Abstract : Background: Current research suggests that physical changes associated with systemic sclerosis (SS) can impact negatively on the sexual activity of a woman and, consequently, of her partner. Skin induration around vaginal opening and breast, articular pain which affect these patients are often cause of decrease in sexual desire and arousal and, therefore, in sexual activity (1-4). Objectives: The aim of this study was to assess the effectiveness of Dermoxen® intimate cream Lenitiva in hydrating and soothing the troubles of the external intimate area and in improving the level of comfort during sexual intercourse. Methods: The authors developed an independent, randomised, double blind clinical trial at the Department of Rheumatology of "A. Galateo" Hospital in San Cesario di Lecce. 76 women affected by systemic sclerosis (aged between 18 and 65 years, mean age 47, 8) treated with Iloprost once a month, were enrolled and divided into two groups: 40 women (SG) followed a specific treatment with Dermoxen® intimate cream Lenitiva; the remaining 36 women (CG) followed a treatment with placebo cream. Patients be positive to Anti SS/A and Anti SS/B were excluded from the trial. The patients of the study group were instructed to do the treatment once a day for a month. The assessment has been done through the administration of quetionnaires Female Sexual Function Index (FSFI) (5), evaluating 6 parameters (desire, arousal, lubrication, orgasm, satisfaction and pain). Results: From the statistical analysis carried out on the FSFI scores obtained from the two groups under investigation, at time 0 and after a month of treatment we found a significant improvement (p<0.05) in the domain related to Lubrication and Satisfaction with reference to the Study group. Moreover, the specific action of the product analysed in the study group seems to determine a very significant improvement (p<0.01) concerning the pain sensation during sexual intercourse. The study group showed significant improvement in the level of moisturization of the external mucous membrane of vagina and, consequently, a reduction of pain during sexual intercourse. The total FSFI score showed significant improvement. These improvements have not been observed in the control group. Conclusions: According to the obtained results, the treatment with Dermoxen® intimate cream Lenitiva seems to be effective in treating problems related to moisturization and lubrication of external genital area in scleroderma women, improving sexual comfort. References: Saad SC, Behrendt AE: Scleroderma and sexuality. J Sex Res 1996; 33: 215-20. Bhadauria S, Moser DK, Clements PJ et al.: Genital tract abnormalities and female sexual function impairments in systemic sclerosis. Am J Obstet Gynecol 1995; 172: 580-7 Wilson D, Goerzen J, Fritzler MJ: Treat- ment of sexual dysfunction in a patient with systemic sclerosis. J Rheumatology 1993; 20: 1446-7. Bhadauria S, Moser DK, Clements PJ et al.: Genital tract abnormalities and female sexual function impairment in systemic scle- rosis. Am J Obstet Gynecol 1995; 172: 580-7. Rosen R, Brown C, Heiman J, et al. The Female Sexual Function Index (FSFI): a multidimensional self-report instrument for the assessment of female sexual function. J Sex Marital Ther 2000;26:191-208 Disclosure of Interest: M. Muratore: None declared, D. Carati Employee of: Ekuberg Pharma, L. Quarta: None declared, E. Quarta: None declared, A. Grimaldi: None declared, D. Costanza: None declared, A. Tinelli: None declared DOI: 10.1136/annrheumdis-2014-eular.5568